Arquitetura residencial verticalizada em São Paulo nas décadas de 1930 e 1940 - Pinheiro, Maria Lúcia Bressan (Anais do Museu Paulista: História e Cultura Material, 2008)
The present work addresses the topic, as yet scarcely studied, of high-rise residential architecture in Sao Paulo during the 1940s and 50s. Supported by some representative case studies, observations were drawn on the following aspects: the strategies used to propagate this new dwelling form, the available aesthetical options for these buildings, the definition of these units' purposes and uses and the development of ground plan architectural solutions. This article aims to render evident the great value and complexity of its subject matter, which is not only extremely important as a theme of Sao Paulo's architectural history, but also, and foremostly, as a significant cultural heritage of this city, which should be acknowledged and safeguarded.